2008
DOI: 10.1063/1.2841694
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the frequency tuning effect in the 14GHz CAPRICE ion source

Abstract: A set of measurements with the CAPRICE ion source at the GSI test bench has been carried out to investigate its behavior in terms of intensity and shape of the extracted beam when the microwaves generating the plasma sweep in a narrow range of frequency (+/-40 MHz) around the klystron center frequency (14.5 GHz). Remarkable variations have been observed depending on the source and the beamline operating parameters, confirming that a frequency dependent electromagnetic distribution is preserved even in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 13 publications
3
34
0
Order By: Relevance
“…The percentage of power that is reflected versus the frequency, Figure 2, is obtained without changing the optimized parameters. As can be seen, sudden variations of plasma coupling can be obtained with small variations of frequency, similar to results observed in [12 ].…”
Section: Interlocksupporting
confidence: 76%
“…The percentage of power that is reflected versus the frequency, Figure 2, is obtained without changing the optimized parameters. As can be seen, sudden variations of plasma coupling can be obtained with small variations of frequency, similar to results observed in [12 ].…”
Section: Interlocksupporting
confidence: 76%
“…However, despite the effect of the magnetic field was expected, a so deep influence of the pumping wave frequency on the structural properties of the plasma is something new. It was indirectly observed at GSI-Darmstadt [17], predicted by theoretical papers [18], but never observed so clearly (and directly into the plasma chamber) up to now. The two points above open wide two interesting issues.…”
Section: Discussion and Comparison With Simulationsmentioning
confidence: 98%
“…Due to the moderate curvature of the magnetic field lines in the near axis region, ions are taken from the near axis regions as well, hence delivered to the extraction hole. Therefore, hollow plasmas will produce lower ion beam currents, and, sometimes, hollow beams as well [17].…”
Section: Discussion and Comparison With Simulationsmentioning
confidence: 99%
“…8,9 A promising newcomer in this "collection of techniques" is the so-called frequency tuning effect (FTE). 10 Experiments with some 2nd generation ECR ion sources have demonstrated that the extracted beam currents are sensitive to microwave frequency variations on the order of 10 MHz. 10,11 It has been argued 12 that the beam current variations associated with the minute frequency shifts are due to the excitation of electromagnetic eigenmodes of the plasma chamber acting as a resonator cavity, and subsequent differences between the electron heating properties that presumably affect the ionization rate and plasma confinement, as well as ion dynamics.…”
Section: Introductionmentioning
confidence: 99%